Challenges faced by teachers in the implementation of curriculum changes for Primary Schools : the case of Mamabolo Circuit, South Africa - Mamabolo, J. M. (African Perspectives of Research in Teaching & Learning, 2021)
This paper investigated challenges faced by ten primary school teachers in the implementation of Curriculum Assessment and Policy Statement (CAPS) programme. The study was inspired by the apparent misinterpretation of teaching and learning programmes by teachers in the implementation of CAPS in schools. In consequence, the theory of assimilation and accommodation was used as a lens to understand how teachers cope with curriculum challenges emanating from the new programme at five primary schools. Furthermore, the interpretive paradigm, which was underpinned by the qualitative methodology, was applied because of its significance and relevance for providing researchers with thick data designed for scholarly research. In order to afford participants an opportunity to express their views on the topic, data were collected through interviews, which will engage them on their lived experiences. Interviews strengthen participants’ ability to explore facts. Participants were selected on the basis of teaching experience. Findings suggest that although the implementation of the new curriculum seems to be a challenge, teachers acknowledge that curriculum change is imperative. Consequently, they realise that it is important to adapt in order to cope with the new demands espoused by the curriculum. Key words: assimilation; accommodation; interpretive paradigm; CAPS; veracity; phenomenon and curriculum
Article published in the African Perspectives of Research in Teaching & Learning (APORTAL) 5(1): 2021
Keywords: Assimilation; Accommodation; Interpretive paradigm; CAPS; Veracity; Phenomenon and curriculum; Curriculum change; Curriculum change -- South Africa; Curriculum-based assessment